Pendapatan Usahatani Semangka (Citrullus vulgaris) di Lahan Gambut Desa Palingkau Sejahtera Kecamatan Kapuas Murung Kabupaten Kapuas - Miva Dian Pangestu; Arief Hidayatullah; Ilhamiyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
This study aims to determine the amount of costs, revenues, revenues, profits, feasibility, sensitivity and problems faced. The research was conducted from September 2021 to December 2021. The method used in this study was purposive sampling with a sample of 20 watermelon farmers. The average implicit cost is Rp.4.071.969 per hectare, the average explicit cost is Rp.16.119.435 per hectare, the total production cost of watermelon farming is Rp.20.191.404 per hectare, with an average income of Rp.46.889.730 per hectare, an average income of Rp.30.770.295 per hectare, and an average profit of Rp.26.698.326 per hectare. The feasibility of watermelon farming with an R/C ratio value of 2,32 (more than one), and a NPV value of 4.079.801 (more than 0), so it can be stated that watermelon farming is feasible to cultivate. Watermelon farming is sensitive to changes in production (ie decreased production), and is not sensitive to changes in production costs, the problems faced are the physical environment/climate, technology and human resources as well as pests and plant diseases.